Stool viruses in babies in Glasgow. 4. Further hospital studies. - Madeley, C. R. (Cambridge University Press, 1982)
The events occurring during the time in hospital of 24 babies were recorded in detail, particularly those related to bowel function. The babies were admitted to a general paediatric unit with various diagnoses a total of 27 times during a six month period. The purpose of the study was to fill gaps in the records of a previous study (Scott et al. 1979) and to try to relate excretion of viruses detectable by electron microscopy to disturbances of bowel function (diarrhoea and/or vomiting). The results showed that a variety of viruses were associated with gastroenteropathy, that virus excretion could occur without disease and that hospital acquisition of virus is not uncommon. Antiobiotic treatment did not appear to precipitate diarrhoea in this small number of babies.